DEVELOPMENT OF AN ANTIFUNGAL BIOPREPARATION BASED ON AZOLLA CAROLINIANA AND EVALUATION OF ITS EFFICACY - Raxmatova Zarina Bahronovna (TADQIQOTLAR, 2026)
Abstract.  Azolla  caroliniana  is  a  rapidly  renewable  aquatic  fern  with  a permanent symbiosis with the nitrogen-fixing cyanobacterium Anabaena azollae. Its biomass contains phenolics, flavonoids, pigments, lipids, tannins and other secondary metabolites that are relevant to antimicrobial and antioxidant performance. The aim of this  study  was  to  develop  a  literature-guided  IMRAD  manuscript  that  proposes  a practical  antifungal  biopreparation  based  on  A.  caroliniana  and  defines  a  realistic efficacy-evaluation framework for laboratory validation. A comparative analysis of recent and foundational studies was used to identify the most promising extraction route, the most responsive target microorganisms, and the main quality indicators for product standardization. Published evidence indicates that methanolic extracts of A. caroliniana  show  the  strongest  documented  activity  against  Geotrichum  candidum, with a mean inhibition zone of 15 mm and a minimum inhibitory concentration (MIC) of 312.5 µg/mL, while activity against Enterococcus faecalis is moderate and Candida albicans remains largely insensitive in crude systems. Nutrient-starvation studies also show  that  phenolics,  flavonoids  and  anthocyanins  increase  under  controlled  stress, suggesting that cultivation strategy can be used to improve raw-material bioactivity before  extraction.  Based  on  the  synthesized  evidence,  the  proposed  biopreparation workflow  includes  biomass  cultivation,  low-temperature  drying,  solvent  screening, activity-guided  fraction  selection,  formulation  into  a  stabilized  liquid  or  wettable powder,  and  evaluation  by  agar  diffusion,  MIC  determination,  phytochemical profiling, stability testing and preliminary cytotoxicity. The article concludes that A. caroliniana is a promising but still under-optimized source of antifungal metabolites. The  best  near-term  application  is  a  species-specific  biopreparation  developed  from medium-polar extracts and standardized against G. candidum. Further research should expand  the  fungal  test  panel,  identify  marker  compounds,  and  establish  safety  and storage limits for real agricultural and food-protection use.